QUO VADIS PENGANGKATAN GUNTUR HAMZAH SEBAGAI HAKIM MAHKAMAH KONSTITUSI DITINJAU DARI ASPEK KONSTITUSIONALITAS : Quo Vadis The Nomination Of Guntur Hamzah As Constitutional Court Judge From The Aspect Of Constitutionality - Berlian Widya Tama; Deka Oktaviana (Constitution Journal, 2023)
The formation of the Constitutional Court (MK) is an embodiment of the concept of checks and balances, the implications of constitutionalism, as well as efforts to administer state administration in accordance with the existing constitution. On November 23, 2022, the President officially appointed Guntur Hamzah as the new MK Judge replacing Aswanto. However, the process of appointing Guntur Hamza as a Constitutional Court Judge has drawn a lot of criticism because it is considered not in accordance with the existing legal process mechanism and is considered unconstitutional. In fact, the process of dismissing the previous judge, namely Judge Aswanto, also violated the law and was illegal and unconstitutional. Nevertheless, the President's attitude towards this appointment is also considered to be less than compromise. The president also seems only to follow the flow and actions of the DPR. This then strengthens the existence of indications of political motives and conflicts of interest behind the appointment of Guntur Hamzah as a Constitutional Court Judge either by the DPR, the President, or other related institutions. In general, this research was conducted to know the quo vadis of the appointment of Guntur Hamzah as a Constitutional Court Judge from a constitutional point of view. The method used in this study is normative juridical by using statutory and conceptual approaches. The data sources used consist of primary data and secondary data which will then be processed using qualitative descriptive data analysis techniques. From the analysis conducted by the author, it was found that the appointment of Guntur Hamzah as MK Judge was declared unconstitutional, there was a supportive attitude from the President towards the appointment of Guntur Hamzah as MK Judge, and there were indications of political motives and Abstrak Pembentukan Mahkamah Konstitusi (MK) merupakan perwujudan konsep check and balance, implikasi dari konstitualisme, serta upaya penyelenggaraan tata negara sesuai dengan konstitusi yang ada. Pada tanggal 23 November 2022 lalu, Presiden secara  resmi mengangkat Guntur Hamzah sebagai Hakim MK baru menggantikan Aswanto. Namun, proses Pengangkatan Guntur Hamzah sebagai Hakim MK telah menuai banyak kritik karena dianggap tidak sesuai dengan mekanisme proses hukum yang ada dan dianggap inkonstitusional. Pada faktanya, proses pemberhentian hakim sebelumnya, yaitu hakim Aswanto juga melanggar hukum dan tidak sah serta inkonstitusional. Kendati demikian, sikap Presiden terhadap pengangkatan ini juga dinilai kurang kompromis. Presiden juga terlihat tampak hanya mengikuti alur dan tindakan DPR. Hal ini kemudian memperkuat adanya indikasi motif politik dan conflict of interest dibalik pengangkatan Guntur Hamzah sebagai Hakim MK baik oleh DPR, Presiden, maupun lembaga terkait lainnya. Secara general, penelitian ini dilakukan dengan tujuan untuk mengetahui quo vadis pengangkatan Guntur Hamzah sebagai Hakim MK ditinjau dari sudut pandang konstitusional. Metode yang digunakan dalam penelitian ini adalah yuridis normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Sumber data yang digunakan terdiri dari data primer dan data sekunder yang kemudian akan diolah menggunakan teknik analisis data deskriptif kualitatif. Dari analisis yang dilakukan oleh Penulis, didapati hasil penelitian bahwa pengangkatan Guntur Hamzah sebagai Hakim MK dinyatakan inkonstitusional, adanya sikap mendukung dari Presiden terhadap pengangkatan Guntur Hamzah sebagai Hakim MK, dan Adanya Indikasi Motif Politik dan Konflik Kepentingan oleh DPR, Presiden, serta Lembaga Terkait dalam Pengangkatan Guntur Hamzah sebagai Hakim MK